1993
DOI: 10.1037/0735-7036.107.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Social experience with siblings fosters species specific responsiveness to maternal visual cues in bobwhite quail chicks (Colinus virginianus).

Abstract: We examined the role of visual and social experience with siblings in the development of bobwhite quail (Colinus virginianus) chicks' preference for species-specific maternal visual cues. Chicks were reared in 1 of 4 conditions: group, isolation, partial isolation, and heterospecific group. They were tested in simultaneous choice tests with species-typical and species-atypical audiovisual stimuli. Results revealed that only subjects that were reared in a group with same-aged conspecifics preferred the visual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 22 publications
(31 reference statements)
4
36
3
Order By: Relevance
“…These results parallel the results of previous studies (Lickliter & Virkar, 1989;McBride & Lickliter, 1993) demonstrating naive chicks' abilities to utilize maternal visual cues by 72 hr following hatching and provides the necessary control group for the subsequent experiments of this study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results parallel the results of previous studies (Lickliter & Virkar, 1989;McBride & Lickliter, 1993) demonstrating naive chicks' abilities to utilize maternal visual cues by 72 hr following hatching and provides the necessary control group for the subsequent experiments of this study.…”
Section: Resultssupporting
confidence: 92%
“…These findings are consistent with previous observations which revealed that unstimulated, group-reared bobwhite quail chicks do not typically emit distress vocalizations (McBride & Lickliter, 1993). These findings are also consistent with previous findings obtained from ducklings (Gaioni & Platte, 1982), in which ducklings were found to attend to other ducklings' distress vocalizations and alternately respond with their own distress calls.…”
Section: Methodssupporting
confidence: 94%
See 2 more Smart Citations
“…These results differ markedly from those obtained from unmanipulated bobwhite chicks in previous studies utilizing identical testing procedures. In these studies, control chicks reliably preferred the species-typical bobwhite hen over the scaled quail hen by 72 hr of postnatal age (Banker & Lickliter, 1993;Lickliter, 1990Lickliter, , 1994Lickliter & Virkar, 1989;McBride & Lickliter, 1993). In the present study, chicks exposed to augmented prenatal tactile and vestibular stimulation did not prefer the bobwhite hen over the scaled quail hen, even by 120 hr of age, indicating that the onset of chicks' visual responsiveness to maternal cues is compromised as a result of augmented prenatal proximal sensory stimulation.…”
Section: Resultscontrasting
confidence: 59%